1993
DOI: 10.1126/science.8391166
|View full text |Cite
|
Sign up to set email alerts
|

Binding of the Ras Activator Son of Sevenless to Insulin Receptor Substrate-1 Signaling Complexes

Abstract: Signal transmission by insulin involves tyrosine phosphorylation of a major insulin receptor substrate (IRS-1) and exchange of Ras-bound guanosine diphosphate for guanosine triphosphate. Proteins containing Src homology 2 and 3 (SH2 and SH3) domains, such as the p85 regulatory subunit of phosphatidylinositol-3 kinase and growth factor receptor-bound protein 2 (GRB2), bind tyrosine phosphate sites on IRS-1 through their SH2 regions. Such complexes in COS cells were found to contain the heterologously expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
142
0
2

Year Published

1996
1996
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 298 publications
(149 citation statements)
references
References 44 publications
5
142
0
2
Order By: Relevance
“…p66 and p52 Shc are strongly phosphorylated in N cells by IGF-I, but are very weakly phosphorylated in one S cell line, SK-N-AS. Whereas Akt is exclusively activated by the PI 3-K pathway and is dependent on IRS protein activation (Franke et al, 1997), MAPK activation through Grb2/SOS-Ras can occur by either IRS or Shc signaling (Baltensperger et al, 1993;Sasaoka et al, 1994). We have previously suggested that Shc, rather than IRS-2, plays a major role in the activation of MAPK in SH-SY5Y cells (Kim et al, 1998a).…”
Section: Discussionmentioning
confidence: 99%
“…p66 and p52 Shc are strongly phosphorylated in N cells by IGF-I, but are very weakly phosphorylated in one S cell line, SK-N-AS. Whereas Akt is exclusively activated by the PI 3-K pathway and is dependent on IRS protein activation (Franke et al, 1997), MAPK activation through Grb2/SOS-Ras can occur by either IRS or Shc signaling (Baltensperger et al, 1993;Sasaoka et al, 1994). We have previously suggested that Shc, rather than IRS-2, plays a major role in the activation of MAPK in SH-SY5Y cells (Kim et al, 1998a).…”
Section: Discussionmentioning
confidence: 99%
“…13,14 For example, the 897 YVNI motif of IRS-1 binds to the growth factor receptor-bound protein 2 (Grb2) adapter molecule, the 1180 YIDL motif binds to Syp protein tyrosine phosphatase, and 613 YMPM and 942 YMKM motifs bind to the p85 subunit of phosphatidylinositol-3 kinase (PI3K). 13,[15][16][17][18][19] The Grb2 binds to PY-IRS-1 19,20 leading to sequential activation of p21 ras , mitogen-activated protein kinase kinase (MAPKK), and MAP kinase (MAPK) [20][21][22][23] (see Fig. 1).…”
Section: Insulin/igf-1/irs-1/mapk Pathway Signaling In Hccmentioning
confidence: 99%
“…These phosphorylation sites then serve as docking sites for several proteins possessing SH2 domains. Thus, phosphorylated IRS-1 binds to and stimulates phosphatidylinositol (PI) 3-kinase, SHPTP-2, and via GRb2-SOS the Ras and mitogen-activated protein (MAP) kinase pathways (11)(12)(13)(14)(15)(16)(17)(18). Although Gly 972 is not directly located in a phosphorylation site, it is conserved in human, rat, and murine IRS-1 and lies between two potential sites of tyrosine phosphorylation involved in binding the p85 subunit of PI 3-kinase.…”
Section: Introductionmentioning
confidence: 99%